2004
DOI: 10.1158/1078-0432.ccr-04-0855
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Hollow Fiber Assay for the Determination of Microtubule DisruptionIn vivo

Abstract: Purpose: The hollow fiber assay is used successfully as a routine in vivo screening model to quantitatively define anticancer activity by the National Cancer Institute. This study investigates whether the hollow fiber assay can be used as a short-term in vivo model to demonstrate specific pharmacodynamic end points, namely microtubule and cell cycle disruption.Experimental Conclusion: These data demonstrate that the hollow fiber assay can be used as a short-term in vivo model for studying the pharmacodynamic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Animal models allow for the pharmacokinetic assessment in a complex in vivo environment that includes the ability for metabolic bioactivation or detoxification that can affect antitumor activity. The in vivo hollow fiber assay is also used as a routine screening method for anticancer activity, since greater than 50 cell lines can be inserted into small fibers that are subsequently implanted into mice to allow for testing in a cost effective manner [11]. Studies that assess drug pharmacokinetics in small animal models are useful for determining minimum effective exposures required for antitumor activity, drug disposition in tissue, and drug-drug interactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Animal models allow for the pharmacokinetic assessment in a complex in vivo environment that includes the ability for metabolic bioactivation or detoxification that can affect antitumor activity. The in vivo hollow fiber assay is also used as a routine screening method for anticancer activity, since greater than 50 cell lines can be inserted into small fibers that are subsequently implanted into mice to allow for testing in a cost effective manner [11]. Studies that assess drug pharmacokinetics in small animal models are useful for determining minimum effective exposures required for antitumor activity, drug disposition in tissue, and drug-drug interactions [12].…”
Section: Introductionmentioning
confidence: 99%
“…The The HFA is currently used by the NCI in the US for secondary drug screening and saves time and labour compared to the classical tumour implantation experiments. Recently, several papers have been published demonstrating that the HFA is also suited for short-term in vivo pharmacodynamic studies (Hall et al, 2000;Leong et al, 2004;Suggitt et al, 2004;Suggitt and Bibby, 2005), thereby using immunocompetent mice for the growth of human cells, without problems such as infiltrating immune cells in this period. Our results showed that the HFA is excellently suitable for studying several pharmacodynamic end points in cancer cells when treated in vivo with fluoropyrimidines.…”
Section: Discussionmentioning
confidence: 99%
“…In the HFA, cytotoxicity is determined using a modified MTT assay, taken into account the in vivo parameters, such as pharmacokinetics and drug transport/pH/pO 2 at tumour site (Phillips et al, 1990;Jonsson et al, 2000). Additionally, several pharmacodynamic end points can also be investigated, such as DNA damage induction, apoptosis or cell cycle analysis (Hall et al, 2000;Leong et al, 2004;Suggitt et al, 2004). This methodology also saves time (assay o2 weeks) and the number of animals used in the experiments.…”
mentioning
confidence: 99%
“…This provides an additional powerful aid to investigate tumor growth and evaluate the morphological effect of drugs on different cell populations that could be used as pharmacodynamic endpoints. 19 The validity of using the HFA to assess the response of the ESFT to toxic agents was demonstrated by maintenance of the sensitivity of ESFT cells to the cell cycle-dependent cytotoxic doxorubicin. 33 Tumor cell proliferation and viable cell counts decreased in a time-and dose-dependent manner after treatment with doxorubicin, demonstrating that adequate levels of doxorubicin to induce cytotoxicity were achieved within the HFs and that the ESFT cells retained their sensitivity to this agent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the HFA has been used to provide quantitative indications of pharmacodynamic and pharmacokinetic endpoints with minimum expenditure of time and materials. [15][16][17][18][19][20][21] Unfortunately, these screens are not useful in identifying agents that may have activity against pediatric and adolescent tumors, because cell lines from these cancers are not presently part of the NCI screening program. Traditionally, new treatment strategies for children have been informed by advances in adult malignancies, with only agents shown to have acceptable toxicity and efficacy in phase I and II trials in adults subsequently evaluated in the pediatric and adolescent population.…”
mentioning
confidence: 99%